1997
DOI: 10.1073/pnas.94.3.967
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional activation of mucin by Pseudomonas aeruginosa lipopolysaccharide in the pathogenesis of cystic fibrosis lung disease

Abstract: An unresolved question in cystic fibrosis (CF) research is how mutations of the CF transmembrane conductance regulator, a Cl ion channel, cause airway mucus obstruction leading to fatal lung disease. Recent evidence has linked the CF transmembrane conductance regulator mutation to the onset and persistence of Pseudomonas aeruginosa infection in the airways, and here we provide evidence directly linking P. aeruginosa infection to mucus overproduction. We show that P. aeruginosa lipopolysaccharide profoundly upr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
217
3
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(230 citation statements)
references
References 22 publications
9
217
3
1
Order By: Relevance
“…MUC2 is approximately 17 kb in size, with 48 exons, and the protein product is more than 5100 amino acids long (20). Its promoter region was the first of the mucins to be elucidated (21). MUC2 is expressed primarily in the small intestine and colon of the GI tract (22), but its mRNA has also been detected in the airways of the lungs (23).…”
Section: Muc2 Expression and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…MUC2 is approximately 17 kb in size, with 48 exons, and the protein product is more than 5100 amino acids long (20). Its promoter region was the first of the mucins to be elucidated (21). MUC2 is expressed primarily in the small intestine and colon of the GI tract (22), but its mRNA has also been detected in the airways of the lungs (23).…”
Section: Muc2 Expression and Regulationmentioning
confidence: 99%
“…Studies of MUC2 in the GI tract and its expression during carcinogenesis reveal that promoter DNA methylation is a frequent mechanism that controls MUC2 expression (142,143). Previous data indicate that the sequence of the MUC2 promoter region approximately 343 bp upstream of the transcription start site contains elements regulating MUC2 expression (21,22). Recent results demonstrate that the methylation level of this region, comprising nine CpG sites, is related to MUC2 expression in colon cancer cells in vitro (143) and pancreatic cancer in vivo (142).…”
Section: Muc2: An Example Of An Epigenetically Controlled Mucin Genementioning
confidence: 99%
“…It also induced mucin secretion from guinea pig tracheal epithelial cells (Fischer et al, 1999). Based on these reports, we investigated whether berberine affects EGF-, PMA-or TNF-α-induced MUC5AC mucin gene expression and mucin production from NCI-H292 cells, a human pulmonary mucoepidermoid cell line which is frequently used for studying intracellular signaling pathways involved in airway mucin production (Li et al, 1997;Takeyama et al, 1999;Shao et al, 2003). As can be seen in Results, berberine inhibited the production of MUC5AC mucin protein induced by EGF, PMA and TNF-α, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Phorbol 12-myristate 13-acetate (PMA) is an inflammatory stimulant affecting gene transcription, cell growth and differentiation and induces MUC5AC gene expression in NCI-H292 cells (Park et al, 2002;Hewson et al, 2004). Based on these reports, we investigated whether baicalin, baicalein or schizandrin affect EGF-and PMA-induced MUC5AC mucin production by NCI-H292 cells, a human pulmonary mucoepidermoid cell line which is frequently used for studying intracellular signaling pathways involved in airway mucin production (Li et al, 1997;Takeyama et al, 1999;Shao et al, 2003). Results showed that baicalin, baicalein and schizandrin each inhibited the production of MUC5AC mucin protein induced by EGF and PMA ( Fig.…”
Section: Discussionmentioning
confidence: 99%